THE PERCEPTION OF THE COMPANION IN THE PROCESS OF CHILDBIRTH - Adelita Deniporte Gonzalez; Elizabete dos Santos Fernandes; Elizangela Fasolo da Silva; Marcelexandra Rabelo; Silvana Regina Rossi Kissula Souza (Universidade Federal do Paraná, 2012)
Childbirth is a period of physiological transition and the World Health Organization recommends humanized actions; among these practices is the presence of a companion during the prenatal check-up, birth and post-natal period. In Brazil, this practice is regulated by law. Considering the importance of family support, the benefits of the companion for the expectant mother and the need for complying with the law, the authors aimed to understand the perception of the companion in the process of childbirth. It is descriptive research with a qualitative approach, carried out in a teaching maternity unit in the period of November 2009 to June 2010. Data collection was carried out through semi-structured interviews, transcribed and submitted to content analysis. The results showed that the companions feel satisfied and notice the importance of their inclusion in the birth process. Although the presence of the companion is not yet a reality in all healthcare institutions, it is relevant to the preparation of the healthcare team to receive the woman and her companion.